2021
DOI: 10.1038/s42003-020-01536-6
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting genetic diversity and gene synthesis to identify superior nitrogenase NifH protein variants to engineer N2-fixation in plants

Abstract: Engineering nitrogen fixation in eukaryotes requires high expression of functional nitrogenase structural proteins, a goal that has not yet been achieved. Here we build a knowledge-based library containing 32 nitrogenase nifH sequences from prokaryotes of diverse ecological niches and metabolic features and combine with rapid screening in tobacco to identify superior NifH variants for plant mitochondria expression. Three NifH variants outperform in tobacco mitochondria and are further tested in yeast. Hydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(65 citation statements)
references
References 49 publications
(50 reference statements)
4
59
0
Order By: Relevance
“…Expression of active NifH (the Fe protein component of the Mo nitrogenase) and NifB (a FeMo-co maturating protein) in mitochondria of S. cerevisiae has proven that these extremely O 2 -sensitive nitrogenase proteins can accumulate in a eukaryotic cell, representing the first steps towards engineering nitrogenase in eukaryotes (L opez-Torrej on et al, 2016;Bur en et al, 2017). Recent studies have also shown that both mitochondria and chloroplasts of tobacco can harbour active NifH at the end of the dark period (Eseverri et al, 2020;Jiang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Expression of active NifH (the Fe protein component of the Mo nitrogenase) and NifB (a FeMo-co maturating protein) in mitochondria of S. cerevisiae has proven that these extremely O 2 -sensitive nitrogenase proteins can accumulate in a eukaryotic cell, representing the first steps towards engineering nitrogenase in eukaryotes (L opez-Torrej on et al, 2016;Bur en et al, 2017). Recent studies have also shown that both mitochondria and chloroplasts of tobacco can harbour active NifH at the end of the dark period (Eseverri et al, 2020;Jiang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Strep-tagged NifU purified from E. coli was reconstituted in vitro as described (31) with slight modifications. 20 μM of NifU dimer was prepared in 100 mM MOPS (pH 7.5) buffer containing 8 mM 1,4-dithiothreitol (DTT) and incubated at 37 °C for 30 min.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are no examples of the other nitrogenase components expressed in C. reinhardtii, although their accumulation has been achieved in plant and yeast mitochondria [19][20][21]24,63,67]. Again, plastid accumulation of the Anf structural subunits (Figure 2C) should be achievable with the correct choice of regulatory elements and environmental conditions (e.g., anaerobiosis) to optimise protein expression.…”
Section: Expression Of the Anf /Nif Genes In The Chloroplast Of C Reinhardtiimentioning
confidence: 99%